(untitled) (Community Based Medical Journal, 2026)
Homicide represents a critical public health and legal challenge in Bangladesh, claiming numerous lives and reflecting underlying social tensions. A precise understanding of its patterns is crucial for informing violence prevention strategies and guiding effective policy and policing interventions. A cross-sectional study was conducted in the Department of Forensic Medicine & Toxicology of Cumilla Medical College, Cumilla, Bangladesh, between July 2024 and June 2025, to assess the patterns of homicidal deaths based on autopsy findings. We analyzed 197 purposively selected homicide cases from autopsy procedures. Data was analyzed using MS-Excel to generate descriptive statistics on victim demographics and injury patterns. Our data revealed that young males (75.6%), particularly in 21–40 years age group (62.4%) were the most common victims. Sharp weapon injuries were the predominant cause of death (47.2%), followed by firearms (24.4%). Most incidents occurred outdoors (51.8%) during night hours (39.6%) and were motivated by interpersonal disputes (41.1%). No significant association was found between the victim’s age and the cause of death (p=0.961). To conclude, young males are the primary victims of homicide, predominantly from sharp weapon injuries in interpersonal disputes. Targeted interventions, including stricter weapon regulation and community conflict resolution programs, are urgently recommended to mitigate this public health burden. CBMJ 2026 January: vol. 15 no. 01 P:121-126